KOMUNIKASI PEMASARAN UNTUK PROGRAM PEMBINAAN REMAJA MASJID - Listi Nur Aziansyah (STID Al-Hadid, 2021)
REMAS is a guidance place for Moslem teenagers. However, REMAS tends to have lack of participants. Dewan Masjid Indonesia also assess that REMAS regeneration is needed in Indonesia. A lack of REMAS progress information is one of the causes of its lack of participants. It results in their perception that REMAS is not interesting. To respond the problem, through this study, a marketing communication for REMAS guidance program has been developed with AIDA approach. It aims to be a reference for REMAS or other da’wah institutions in conducting marketing communication for Moslem teenagers’ guidance program. This basic research uses qualitative literature approach. It indicates that Moslem teenagers actually need this program since they are finding their self-identity, examining the right life attitude and moral standards, and wanting to know more about Islam. These problems need to be communicated to them by using AIDA, namely communicating the matters through response stages. It starts from triggering the awareness on the need of REMAS guidance program and answering their perception about REMAS (Attention). Then, they need to get information about description, benefits and analysis on answering their needs through the program (Interest and Desire). And finally, they need to join the program (Action).